The Analysis of Adaptive reuse Implementation Principles at Tanatap Coffee Braga - Azmi Fadila Zulfikar; Rizki Lukman Hakim; Tyas Santri (Department of Architecture, Faculty of Engineering, University of Muhammadiyah Aceh, 2026)
The Braga District in Bandung is one of the city’s unique areas, rich in historical significance due to its row of colonial buildings. However, the district currently faces significant challenges due to the tide of modernization and the demands of urban functionality. The principle of adaptive reuse is one of the alternative solutions often employed as a strategy for addressing the context of historic building restoration and renovation. This approach repurposes buildings that are to be preserved due to their historical value, transforming them into new functions without compromising their inherent value. Tanatap Coffee Braga is a commercial establishment that has attempted to implement adaptive reuse by integrating modern commercial functions with efforts to preserve cultural heritage. This study aims to conduct an in-depth analysis of the application of adaptive reuse principles to the subject of study in support of the preservation of historic architecture. This is a qualitative study involving data collection through direct field observations and a review of relevant literature, followed by descriptive data analysis. The results of the study indicate that Tanatap Coffee Braga has made efforts to preserve the original architectural elements and visual character that serve as the main attraction of the area, while also integrating them with new, adaptive functions. The implementation of this approach is categorized as “low-intervention adaptive reuse” because it involves no major changes to the main facade, but rather interventions in the floor structure (voids), reflecting a compromise between commercial function and conservation principles. This integration model is considered relevant for adoption in other cultural heritage areas in Indonesia to support sustainable urban development.